Effect of different simulated altitudes on repeat sprint performance in team sport athletes - Goods, P.; Dawson, B.; Landers, G.; Gore, C.; Peeling, P. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Purpose: This study aimed to assess the impact of three simulated altitude exposure heights on repeat sprint performance in team sport athletes. Methods: Ten trained male team sport athletes completed three sets of repeated sprints (9 x 4 s separated by varying recovery jogging times and 3 min rest between sets) on a non-motorised treadmill (Woodway Force 3.0) at sea-level or at simulated altitudes of 2000, 3000 and 4000 m. Participants completed four trials in a random order over 4 weeks, with total work (J), mean power output (MPO), peak power output (PPO), blood lactate concentration (BLa) and oxygen saturation (SaO2) recorded after each set. Results: Each increase in simulated altitude corresponded with a significant decrease in SaO2. Total work across all sets was highest at sea-level and correspondingly lower at each successive altitude (p<0.05; sea level 158914 ± 13094 J > 2000 m 149046 ± 10124 J > 3000 m 141126 ± 11083 J > 4000 m 127466 ± 8519 J). In the first set, MPO was lower at 4000 m only, but for subsequent sets 2 & 3, decreases in MPO were observed at all altitudes (p<0.05; sea-level > 2000 m > 3000 m > 4000 m). Sea-level PPO was maintained in all sets except for set 3 at 400 m (p<0.05, 4000 m 1661 ± 520 W < sea level 2135 ± 365 W and 2000 m 2125 ± 376 W). Blood lactate levels at 4000 m were significantly greater (p<0.05) than at sea-level after all sets, whereas BLa at 3000 m was only elevated compared to sea-level in the final 2 sets, and at 2000 m BLa was unchanged compared to sea-level. Conclusions: These results suggest that when completing intermittent hypoxic training, higher may not be better, since a simulated altitude of 4000 m may potentially blunt absolute training quality. Therefore, it is recommended that a moderate simulated altitude (2000-3000 m) be employed when implementing intermittent hypoxic repeat sprint training for team sport athletes to maintain training output while adding a hypoxic stimulus. However, the possibility of the increased metabolic cost at 4000 m having some positive outcome on performance cannot be discounted and should be further investigated in a training study.